2022
DOI: 10.3390/su14148674
|View full text |Cite
|
Sign up to set email alerts
|

Driving Forces of Tourism Carbon Decoupling: A Case Study of the Yangtze River Economic Belt, China

Abstract: Although decoupling tourism growth from carbon emissions is vital for sustainable tourism development, the driving forces of tourism carbon decoupling in the Yangtze River Economic Belt (YREB) are little known. Herein, our study applies the geo-detector model and the Tapio decoupling index to investigate the decoupling trend and driving mechanism of the tourism economy in the YREB from carbon emissions from 2009 to 2019. Our results show that (1) the tourism carbon decoupling status has gradually evolved from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The exploration of the relationship between economic growth and carbon emissions is becoming a hot research topic [11,25]. Many scholars have used the Tapio decoupling model to study this relationship [26][27][28]. However, the Tapio decoupling model is a non-parametric model, unable to accurately characterize the extent of the impact of economic growth on carbon emissions.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The exploration of the relationship between economic growth and carbon emissions is becoming a hot research topic [11,25]. Many scholars have used the Tapio decoupling model to study this relationship [26][27][28]. However, the Tapio decoupling model is a non-parametric model, unable to accurately characterize the extent of the impact of economic growth on carbon emissions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This suggests that increased spending in the tourism sector, likely driven by higher disposable incomes and economic prosperity, contributes to an increase in CO 2 emissions. The variable response of the scale effect suggests that while economic growth can lead to an increase in tourist numbers, the resultant impact on CO 2 emissions can be moderated by implementing sustainable tourism and transportation policies [26,28].…”
Section: Pvarmentioning
confidence: 99%
“…Te Yangtze River Delta region, located at the intersection of the two national strategies of the "Yangtze River Economic Belt" and the "Belt and Road," is one of the world-class urban clusters in China [23]. As shown in Figure 1, it is a region with dense urban agglomeration, high urbanization, and a relatively complete industrial chain, including three provinces and one municipality, namely, Jiangsu, Zhejiang, Anhui, and Shanghai [24]. In 2019, the Chinese government ofcially released "the Outline of the Regional Integrated Development Plan of the Yangtze River Delta," making the Yangtze River Delta region a community with shared interests and a shared future.…”
Section: Study Areamentioning
confidence: 99%
“…Considering that tourism is a strategic industrial pillar for China's economy, it is essential to comprehend the connection between the TE and TCDE to achieve both China's carbon peaking and carbon neutrality goals and the sustainable tourism of the World Tourism Organization. A number of studies have found evidence that China's tourism industry is transitioning to a low-carbon industry 23 , 28 30 . However, there are 34 provincial administrative regions throughout China, and the development of tourism in each region is obviously different 31 , 32 .…”
Section: Introductionmentioning
confidence: 99%